2010
DOI: 10.1177/1077559510370365
|View full text |Cite
|
Sign up to set email alerts
|

Making Meaning of Traumatic Events: Youths’ Strategies for Processing Childhood Sexual Abuse are Associated With Psychosocial Adjustment

Abstract: The need to make meaning of childhood sexual abuse (CSA) is common and often persists long after the abuse ends. Although believed to be essential for healthy recovery, there is a paucity of research on how youth process their CSA experiences. The current study identified individual differences in the ways youth process their CSA and examined associations with psychosocial adjustment. A sample of 108 youth with confirmed abuse histories enrolled in the study within 8 weeks of abuse discovery, when they were be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 47 publications
(73 reference statements)
7
67
1
4
Order By: Relevance
“…Previous studies have shown that treating women who have experienced chronic abuse can be more challenging, as these women demonstrate more negative consequences and treatment outcomes than their nonabused peers (e.g., Charney, Palacios-Boix, & Gill, 2007;Sacks, McKendrick, & Banks, 2008; T. L. Simpson & Miller, 2002). These findings might reflect how childhood and adolescence are critical periods of development, and suggest that women process and make meaning of traumatic experiences during childhood in different ways than they do during adulthood (Simon, Feiring, & McElroy, 2010). The nature of partner violence, where the abuser is also a romantic partner, could also impact how women process and make meaning of the abuse.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have shown that treating women who have experienced chronic abuse can be more challenging, as these women demonstrate more negative consequences and treatment outcomes than their nonabused peers (e.g., Charney, Palacios-Boix, & Gill, 2007;Sacks, McKendrick, & Banks, 2008; T. L. Simpson & Miller, 2002). These findings might reflect how childhood and adolescence are critical periods of development, and suggest that women process and make meaning of traumatic experiences during childhood in different ways than they do during adulthood (Simon, Feiring, & McElroy, 2010). The nature of partner violence, where the abuser is also a romantic partner, could also impact how women process and make meaning of the abuse.…”
Section: Discussionmentioning
confidence: 85%
“…PTC was assessed from the semi-structured Trauma-Meaning Making Interview (TMMI; Simon, Feiring, & McElroy, 2010), which asks participants to describe their maltreatment; express their thoughts and feelings about the maltreatment and its discovery at the time it happened as well as over time; and to explain the perceived effects of their maltreatment experiences. For the current study, questions were added about the perceived impact of their CM experiences on becoming a parent and the parent–child relationship.…”
Section: Methodsmentioning
confidence: 99%
“…Studies with young people who have experienced sexual abuse as children yield suggestive findings. Simon, Feiring, & Kobielski McElroy (2010) reported that 6 years after disclosure, only a minority of young people reported coherent narratives reflecting understanding of their abuse memories (defined as, for example, recounting from the point of view of themselves as children but retaining a present focus, constructing a causal understanding of their abuse). In contrast, the majority of participants (who also manifested greater trauma symptomatology) provided confusing, overly detailed, or very brief memories which, according to the researchers, suggested that they had difficulty making sense of the experience and were experiencing overwhelming emotion or avoidance.…”
Section: Poor Narrative Abilitymentioning
confidence: 99%